2014
DOI: 10.3109/14756366.2014.979347
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of resveratrol–salicylate hybrid derivatives as CYP1A1 inhibitors

Abstract: Resveratrol and aspirin are known to exert potential chemopreventive effects through modulation of numerous targets. Considering that the CYP450 system is responsible for the activation of environmental procarcinogens, the aim of this study was to design a new class of hybrid resveratrol-aspirin derivatives possessing the stilbene and the salicylate scaffolds. Using HepG2 cells, we evaluated (a) the inhibition of TCDD-mediated induction of CYP1A1 exerted by resveratrol-aspirin derivatives using the EROD assay,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…In this regard, we have recently reported the chemical synthesis and CYP1A1 inhibitory profile of a new series of hybrid resveratrol-salicylate analogues with promising chemopreventive activity (38); after we re-examined the chemical structures of these derivatives, we recognized a potentially useful pattern: by replacing the central methylene group in NSC14778 for the ethylene (CH=CH) moiety present in stilbenes. It is noteworthy that we identified some structural similarities between NSC14778, and our recently reported salicylate-resveratrol analogues, so that it was reasonable to predict certain degree of DNMT inhibition by our molecules (however, please note that we did not start the design of our salicylate-resveratrol derivatives based on the docking pose of NSC14778).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this regard, we have recently reported the chemical synthesis and CYP1A1 inhibitory profile of a new series of hybrid resveratrol-salicylate analogues with promising chemopreventive activity (38); after we re-examined the chemical structures of these derivatives, we recognized a potentially useful pattern: by replacing the central methylene group in NSC14778 for the ethylene (CH=CH) moiety present in stilbenes. It is noteworthy that we identified some structural similarities between NSC14778, and our recently reported salicylate-resveratrol analogues, so that it was reasonable to predict certain degree of DNMT inhibition by our molecules (however, please note that we did not start the design of our salicylate-resveratrol derivatives based on the docking pose of NSC14778).…”
Section: Resultsmentioning
confidence: 99%
“…To study the in vitro DNMT inhibition exerted by the salicylate-resveratrol analogues reported previously (38), we used a filter paper based Scintillation Proximity Assay (SPA) (42). We used the well-known DNMT inhibitor (altough structurally unrelated) S-adenosyl-L-homocysteine (SAH)(54, 55) as the standard which showed IC 50 = 2 μM on DNMT1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The roles of GSTM1, XRCC1, XRCC3, CYP2D6, and C188T genes have been studied thoroughly. However, the cytochrome P450 (CYP) 1A1 gene has not been studied extensively, and the results so far are confusing (Aldawsari et al, 2014;Wohak et al, 2014). Several studies (Lee et al, 2010;Arinc et al, 2014;Henderson et al, 2014;Wang et al, 2014;Gaspar-Ramirez et al, 2015) have shown that patients with CYP1A1 deletion cannot produce the active enzyme, so that carcinogenic substances cannot be metabolized and excreted.…”
Section: Introductionmentioning
confidence: 99%